Nanocasting nanoporous nickel oxides from mesoporous silicas and their comparative catalytic applications for the reduction of p-nitrophenol - Fadhli; Erika, Denanti; Mardiana, St; Rasrendra, Carolus B.; Khalil, Munawar; Kadja, Grandprix T.M. (Chemical physics letters, 2022)
[Display omitted] •Nanoporous nickel oxides were fabricatied by nanocasting.•MCM-41 and KCC-1 were used as the mesoporous silica templates.•The resulting nanoporous nickel oxides resembled a replica of each template's inner architecture.•Nanoporous nickel oxides are used for the reduction of p-nitrophenol.•NiO-MCM presents higher catalytic properties than NiO-KCC due to a better improved molecular diffusion. Herein, nanoporous nickel oxides were prepared through nanocasting using ordered- and less-ordered mesoporous silica templates, i.e., MCM-41 and KCC-1, respectively. The products resembled the replica of the inner architecture of each template. NiO-MCM-41 (nanocasted in MCM-41) possessed a highly ordered structure originating from the arrangement of nanorods resulting in a large specific surface area of 53 m2 g−1. On the other hand, NiO-KCC-1 (nanocasted in KCC-1) exhibited the combination of ordered nanorod and non-ordered foam-like structures with a less specific surface area of 23 m2 g−1. Ultimately, the catalytic tests in the reduction of p-nitrophenol (p-NP) with sodium borohydride (NaBH4) demonstrated that NiO-MCM-41 had significantly higher activity (kobs = 0.25 min−1) and better reusability (p-NP conversion of 92% after 3 times reactions) than those of NiO-KCC-1 (kobs = 0.14 min−1 and a 35% p-NP conversion after 3 times reactions) due to the more improved molecular diffusion within a highly ordered structure. The preferred mechanism was found to follow the Langmuir–Hinshelwood route in which both reactants (p-NP and [BH4]−) were initially adsorbed onto the surface of the catalyst.